Record of partial albino in the scalloped hammerhead Sphyrna lewini (Carcharhiniformes, Sphyrnidae) in the Mexican Pacific Ocean - Hernández-Corona, Jesús Leonardo; Wakida-Kusunoki, Armando T.; Anislado-Tolentino, Vicente (Revista de Biología Marina y Oceanografía, 2022)
This study reports the capture of a partial albino scalloped hammerhead Sphyrna lewini in Puerto Madero, Chiapas, Mexico. The specimen was a neonate female that measured 491 mm total length and had a total weight of 800 g. This is the first report of an albino scalloped hammerhead Sphyrna lewini in the Pacific Ocean and the second in the world. The presence of albinism could be the result of multifactorial events, although anthropogenic stressors such as excessive fishing pressure and marine pollution might be involved.